Prison in Review of Islamic Criminal Law: Between Human and Deterrent Effects - Haq, Islamul (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2020)
This study aims to find out how the prison system is in Islamic criminal law and how to treat prisoners in Islamic criminal law. This research is a qualitative study using a philosophical approach. The analysis of this research uses descriptive analysis method. The results of this study indicate that Islam views prison as a type of takzir punishment. with imprisonment, a prisoner can get a deterrent effect. However, that does not mean that prisoners are treated inhumanely. Islam has principles and ethics that apply to prisoners. One of the noble guidelines of Islam is to treat prisoners well, but is not privileged.